2020
DOI: 10.1016/j.bpj.2019.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Role of Actin Cytoskeleton in Dynamics and Function of the Serotonin1A Receptor

Abstract: G protein-coupled receptors (GPCRs) are important membrane proteins in higher eukaryotes that carry out a vast array of cellular signaling and act as major drug targets. The serotonin 1A receptor is a prototypical member of the GPCR family and is implicated in neuropsychiatric disorders such as anxiety and depression, besides serving as an important drug target. With an overall goal of exploring the functional consequence of altered receptor dynamics, in this work, we probed the role of the actin cytoskeleton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 76 publications
2
32
0
Order By: Relevance
“…The actin cytoskeletal network underlying the plasma membrane was initially not considered as a constituent of the plasma membrane ( 10 ). However, in the past few years, a number of observations using high-resolution microscopic techniques have established the concept of actin cytoskeleton dependent function and dynamics of membrane proteins ( 11 , 12 , 13 , 14 ) and have led to the “anchored protein picket model” of membranes ( 15 ). In addition, a model involving crosstalk between membrane cholesterol and actin cytoskeleton is emerging based on observations such as reorganization of the cortical actin cytoskeleton due to depletion of plasma membrane cholesterol ( 16 ).…”
mentioning
confidence: 99%
“…The actin cytoskeletal network underlying the plasma membrane was initially not considered as a constituent of the plasma membrane ( 10 ). However, in the past few years, a number of observations using high-resolution microscopic techniques have established the concept of actin cytoskeleton dependent function and dynamics of membrane proteins ( 11 , 12 , 13 , 14 ) and have led to the “anchored protein picket model” of membranes ( 15 ). In addition, a model involving crosstalk between membrane cholesterol and actin cytoskeleton is emerging based on observations such as reorganization of the cortical actin cytoskeleton due to depletion of plasma membrane cholesterol ( 16 ).…”
mentioning
confidence: 99%
“…In addition, a recent study has reported that by manipulating GPCRs in host cells, mycobacteria could suppress host cell signaling pathways (Alaridah et al 2017). In this overall context, previous work from our group has highlighted the role of the actin cytoskeleton in the function and dynamics of GPCRs (Ganguly et al 2008;Shrivastava et al 2020). The ability of the actin cytoskeleton to modulate function of membrane proteins involved in pathogen recognition by host cells could provide a molecular basis underlying the role of the actin cytoskeleton in mycobacterial entry.…”
Section: Discussionmentioning
confidence: 93%
“…We have stably expressed the human serotonin 1A receptor in human embryonic kidney (HEK) 293 cells and demonstrated that the receptor exhibits characteristic ligand binding, G-protein coupling, lateral dynamics, and intracellular trafficking, highlighting functional receptor expression in these cells (32,33). As a downstream response to agonist stimulation, the serotonin 1A receptor is known to activate the G i /G o class of G-proteins in HEK-293 cells (34).…”
Section: Cholesterol-dependent Signaling By Serotonin 1a Receptorsmentioning
confidence: 99%